Performance and blood parameters of Holstein/Zebu crossbred heifers fed with two tannins sources (Research, Society and Development, 2020)
The present research objective was to evaluate the performance and blood parameters of lactating cows fed with a diet of two tannin sources, based on sorghum (condensed tannin)  with increasing concentrations of tannic acid (hydrolyzable tannin’s). Increasing levels of tannic acid in a sorghum-based diet for five Holstein/Zebu crossbred lactating cows were subject to a 5 × 5 Latin square experimental design. To assess the effect on cow intake, digestibility, milk production, and blood parameters. All cows received 9.87 kg/DM of corn silage as roughage and 6.38 kg of concentrate consisting of 2.58 kg/DM of ground sorghum 0.87 kg/DM of cornmeal 1.32 kg/DM of soybean bran 0.44 kg/DM of wheat bran 0.2 kg/ DM of urea and 0.18 kg/ DM of mineral mixture. Diet 1 (control) contained low-tannin sorghum and the other diets contained high-tannin sorghum. The levels of tannic acid added to the diets were established based on the quantity of condensed tannin in high-tannin sorghum. Thus, diets 2, 3, 4 and 5 were supplemented with 1.5g (13.%DM), 79.5g (2.6%DM), 157.5g (3.9%DM) and 235.5g (5.2%DM) of tannic acid, totalling 0.078, 0.156, 0.234 and 0.321 total tannin kg/day respectively, to assess the effect on microbial protein synthesis. The diets contained 35 kg of corn silage (roughage) and 6.40 kg of concentrate. The natural and dry matter intake did not significantly differ between groups, except for ether extract (EE) intake that significantly differed. The DM apparent digestibility, crude protein, EE, neutral detergent fiber, total carbohydrate, and non-fibrous carbohydrate did not differ (P > 0.05) with the increase in dietary tannin supplementation. The GOT levels increased linearly. The blood glucose, triglyceride, and cholesterol (total, LDL and HDL) levels did not significantly differ. Hemoglobin showed a significant difference. No significant difference in urea, creatinine and uric acid occurred. Diets using two tannins sources supplementation caused no decrease in the dietary intake or digestibility in the animals. The GOT level changed significantly, showing linear behavior, however below the toxicity level, without any change in the other blood parameters. Milk production decreased with the increase in dietary tannin supplementation.